Twitter Information Representation using Resource Description Framework - Sabah Hadi, Asaad; Mahdi Abdulshaheed, Enass (International Journal of Engineering and Technology, 2018)
Social media service emerged as essential forums for negotiating and giving comments about news, events happening around the world. Such user-generated information can be important data source for researches.Twitter is a micro-blogging which is growing rapidly in the last years.Due to the fast evolution of twitter, the Researchers study tweetsâ€™ content characteristics, so this can help in extraction of information like usersâ€™ information, opinions about topics and other useful information from tweets.This work proposed a method to extract useful data from tweet object and represent it in Resource description framework (RDF) data model. The Streaming API used to collect twitter data by filtering the results based on specific keywords. The response obtained as Java Script Object Notation (JSON) file,then while parsing the obtained file thetweetâ€™s text preprocessing and extract useful information from other entities of tweet object, Jena API used to represent extracted data in RDF data model and save it in RDF file to be used in future applications.Â